Asset Ownership, Investor Protection and Technology Adoption. Issue 2 (2nd April 2020) - Kim, Yong
ABSTRACT: In market economies, agents who provide labour are distinct from investors who own assets. This paper highlights how such an 'investor ownership' arrangement mitigates an external finance problem, especially when new ideas and technologies are adopted in production. When agents are credit constrained, assigning asset ownership to investors, and hold up can be seen as a commitment device that leads to better outcomes. The feature that assets can be used to hold up agents is a productive attribute which I model as an output of production: assets which have been used in past production embody this attribute, and assets which have not, do not. The analysis predicts (i) the share of project specific assets owned by investors increases over time, and (ii) project specific asset values increase then decrease over time, both resulting from a staged financing of new projects. The paper emphasises the importance of investor protection: bargaining power vis-à-vis the agents who produce. Lowering investor protection results in lower production scale and TFP, through partial and general equilibrium effects.